Neem leaf glycoprotein mediated epigenetic modification in oral squamous cell carcinoma - Arya Chatterjee; Arunangsu Singh; Geetha Shanmugam; Sudeshna Rakshit; Latika M Mohanty; Ashok Kumar; Sitaram Harihar; Koustav Sarkar (Elsevier, 2023)
Background: Recent studies have found out that the initiation and progression of cancer, traditionally seen as a genetic disease, is now realized to involve epigenetic abnormalities along with genetic alterations. Studies also emphasize development of drugs targeting histone deacetylases (HDACs) and DNA methyltransferase inhibitors as an emerging anticancer strategy. Oral squamous cell carcinoma (OSCC) is a deadly disease that comprises 60% of all head and neck squamous cell cancers. The leaves of the Neem tree (Azadirachta indica) have been used in traditional Ayurvedic medicine for centuries to treat numerous oral maladies and are known to have significant anti-inflammatory properties. NLGP (a glycoprotein isolated from neem leaf) is famous for its potent anti-inflammatory, immunostimulatory and anti-cancer properties. Thus, in the current research proposal we investigated the NLGP mediated various epigenetic modifications in Oral squamous cell carcinoma (OSCC). Purpose: The aim of this work was to clarify if the epigenetic changes in oral squamous cell carcinoma could be mediated by Neem Leaf Glycoprotein (NLGP), which has already been demonstrated as a potent anti-cancer drug. The study's objectives were further expanded to include investigating the impact of NLGP-mediated epigenetic alterations on the Wnt and PI3K pathways. Study Design: In this research work, we would like to show the epigenetic modification mediated by NLGP on OSCC cell line, SSC-9. We would also like to investigate the involvement of NLGP in certain signal transduction pathway(s) which may play a crucial role in epigenetic modification of oral squamous cell carcinoma. Methodology: ChIP assays were performed with MNase-digested chromatin isolated from the NLGP treated and non-treated SCC-9 cells after fixing protein-DNA interactions with 1% formaldehyde. ChIP-grade antibodies and their isotype-Ig antibodies were used to pull-down DNA:Protein complexes. ChIPed samples were used for quantitative polymerase chain reaction (qPCR) analysis and the derived Ct values converted to absolute copy numbers using cloned-DNA plasmid standard dilution curve. Nonspecific signals obtained with IgG-ChIP were subtracted from test samples. Whole cell extracts were prepared from NLGP-treated and non-treated SSC9 (Oral Cancer Squamous) cells with the help of Cell Lysis Buffer (Sigma). Using differentially treated whole cell extracts coimmunoprecipitations were performed with the Universal Magnetic Co-immunoprecipitation kit (Active Motif), as per the manufacturer's specifications. Single blot was sequentially reprobed with multiple antibodies. For each co-immunoprecipitation experiment, isotype IgG antibody served as a negative control and immunoblotting the corresponding whole cell extracts with the primary antibody served as a positive control (input), and most images presented are from the same experiment and same gel exposure. Result: Treatment with NLGP increased percentage enrichment of Histone H3 trimethylation (H3K4me3) and acetylation (H3K14Ac) markers and decreased percentage enrichment of Histone H3 demethylation (H3K9me3, JMJD3) and deacetylation (HDAC1) markers respectively on DNA repair gene loci (ATM, ATR, DDB2), tumour suppressor gene (TP53), Signal transducer and activator of transcription 1 (STAT1) and DNA-dependent RNA polymerase (RNApol2). On further investigation of the molecular pathways that may be involved, we found that NLGP treatment blocks the activation of the DNA PKCs, a component of the Akt pathway and its subsequent phosphorylation of H2AFX and it also inhibits ß-catenin, an integral molecule of the Wnt pathway via increased percentage enrichment of the tri-methylation (H3K4Me3) and acetylation (H3K14Ac) markers thus inhibiting tumorigenesis and cancer progression in OSCC. Conclusion: Neem Leaf Glycoprotein has been successfully involved in immuno-regulating the various aspects of the immune system in order to mount an effective anti-cancer action and thus has come forward as an emerging cancer-therapeutic strategy based on natural products. This study also contributes to a better understanding of NLGP's epigenetic modulatory function and paves the path for epigenetic-based therapy for OSCC.